Analysis Of Stakeholder Collaboration In The Emergency Management System (PSC) For Forest Fire Disaster Management Based On Pulang Pisau Regent Regulation Number 4 Of 2022 - Lambang Suncoko; Nina , Nina (Sean Institute, 2024)
Pulang Pisau Regency is an area thathas a potential danger of forest and land fires (karhutla) at a moderate to high level. As an area with the potential for disaster events, this has the potential to become an emergency threat to the surrounding community. To overcome this, the Regional Government through the Public Safety Center (PSC) collaborates with various organizations and volunteers from the local community in an emergency management system for handling fire disasters. The aim of this research is to conduct an analysis of stakeholder collaboration in the Emergency Management System (PSC) for forest fire disaster management based on Pulang Pisau Regent Regulation Number 4 of 2022. The research was conducted from October 2023 to March 2024 using a qualitative descriptive research design. Data collection was carried out through observation, interviews and documentation. Researchers conducted interviews with several informants, such as the Head of BPBD Pulau Pisau Regency, company managers, University Public Relations, Police Agency/Polres Public Relations, Head of NGOs, and local residents. In this study, researchers determined informants using the technique of determining informants with certain considerations. The data analysis technique used is a qualitative data analysis technique based on the opinion of Miles & Huberman, which includes data reduction, presentation. The results of this research show that collaboration between BPBD and stakeholders is a key element in managing forest fire disasters with steps that have been identified and implemented. to overcome existing obstacles in collaboration. Things that can be implemented include socializing regulations, preparing disaster management plans, training officers and volunteers, monitoring weather and fire conditions, cross-sector cooperation, and strengthening human resources and technology.